The Neurocognitive and MRI Outcomes of West Nile Virus Infection: Preliminary Analysis Using an External Control Group - Murray, Kristy O.; Nolan, Melissa S.; Ronca, Shannon E.; Datta, Sushmita; Govindarajan, Koushik; Narayana, Ponnada A.; Salazar, Lucrecia; Woods, Steven P.; Hasbun, Rodrigo (Frontiers in Neurology, 2018)
To understand the long-term neurological outcomes resultant of West Nile virus (WNV) infection. Participants from a previously established, prospective WNV cohort were invited to take part in a comprehensive neurologic and neurocognitive examination. Those with an abnormal exam finding were invited for MRI to evaluate cortical thinning and regional brain atrophy following infection. Correlations of presenting clinical syndrome with neurologic and neurocognitive dysfunctions were evaluated, as well as correlations of neurocognitive outcomes with MRI results. From 2002-2012, a total of 262 participants with a history of WNV infection were enrolled as research participants in a longitudinal cohort study, and 117 completed comprehensive neurologic and neurocognitive evaluations. Abnormal neurological exam findings were identified in 49% (57/117) of participants, with most abnormalities being unilateral. The most common abnormalities included decreased strength (26%; 30/117), abnormal reflexes (14%; 16/117), and tremors (10%; 12/117). Weakness and decreased reflexes were consistent with lower motor neuron damage in a significant proportion of patients. We observed a 22% overall rate of impairment on the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), with impairments observed in immediate (31%) and delayed memory (25%). On MRI, participants showed significant cortical thinning as compared to age- and gender-matched controls in both hemispheres, with affected regions primarily occurring in the frontal and limbic cortices. Regional atrophy occurred in the cerebellum, brain stem, thalamus, putamen, and globus pallidus. This study provides valuable new information regarding the neurological outcomes following WNV infection, with MRI evidence of significant cortical thinning and regional atrophy; however, it is important to note that the results may include systemic bias due to the external control group. Considering no effective treatment measures are available, strategies to prevent infection are key.